Remooring: A Qualitative Focus Group Exploration of How Educators Maintain Identity in a Sea of Competing Demands. (January 2019) - Jauregui, Joshua; O'Sullivan, Patricia; Kalishman, Summers; Nishimura, Holly; Robins, Lynne
Abstract : Purpose: Longitudinal faculty development programs (LFDPs) are communities of practice (CoPs) that support development of participants' educator identity (EID). This study explored how program graduates negotiated their newly formed EIDs among competing identities and demands in academic medicine. Method: In this multicenter, cross-sectional, qualitative study, graduates of two LFDP cohorts (one and five years post graduation) were invited in 2015 to participate in a one-hour, cohort-specific focus group. The focus group included questions about views of themselves as educators, experiences of transition out of the LFDP, and sustainability of their EID following program participation. Researchers analyzed transcripts using Wenger's CoP and Tajfel's social identity theories to guide interpretation of findings. Results: Thirty-seven graduates, 17 from one year and 20 from five years post graduation, participated in eight focus groups. They described developing a new EID in their LFDP CoPs. Three major themes emerged: context, agency, and identity. A push–pull relationship among these themes influenced faculty members' EID trajectory over time. Graduates described feeling unmoored from their LFDP community after graduation and relied on individual agency to remoor their new identities to supports in the larger institutional context. Conclusions: LFDP graduation represented a transition point. Graduates found it challenging to lose supports from their time-limited CoP and remoor their EIDs to workplace supports. Remooring required individual agency and external support and affirmation. Faculty development programs must be designed with transition periods and sustainability in mind to ensure that participants and institutions can benefit from their transformative effects over time. Abstract : Supplemental Digital Content is available in the text.